Lung ultrasound assessment of pulmonary effects of large patent ductus arteriosus in extremely preterm infants beyond the transitional period - Elhanafy, Thanaa; Nasef, Nehad; Ibrahim, Jenna; Awadalla, Rana; Jain, Amish; Mohamed, Adel (The Ultrasound Journal, 2025)
Background: Several studies have suggested a positive association between elevated lung ultrasound scores (LUS) and large patent ductus arteriosus (L-PDA), although findings remain inconsistent. Lung ultrasound score, a semi-quantitative measure of pulmonary aeration loss, has been proposed as a surrogate marker of excessive lung fluid, which may reflect the hemodynamic burden of a significant PDA. The aim of this study was to assess the association between LUS and L-PDA in preterm neonates beyond the initial transitional period and examine its correlations with echocardiographic measures of ductal shunting. This is a cohort retrospective study that included preterm infants born at